Polymer emulsion, preparation method and application method of polymer emulsion in preparation of thick coating type polymer cement coating

By combining the polymer emulsion synthesized by special processes with cement powder, thick-coated polymer cement coatings are solved, and the cracking and opening time in existing coatings are achieved, and efficient construction and good film formation effects are achieved.

CN119798523APending Publication Date: 2025-04-11SHANGHAI BAOLIJIA NEW MATERIAL CO LTD

Patent Information

Application Number
CN202510090588.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing polymer cement coatings are prone to cracking during construction and have a short opening time, which affects the construction progress and film formation density.

Method used

A polymer emulsion is used, including monomers such as styrene, butyl acrylate, isooctyl acrylate, etc., emulsifiers, initiators and additives, and synthesized through a special process to obtain a polymer emulsion with low viscosity and coarse particle size, which is used to compound with inorganic powders such as cement to form thick-coated polymer cement coatings.

Benefits of technology

The polymer cement coating has been achieved at one-time construction to meet the standard thickness, extend the opening time, reduce the initial slurry viscosity, inhibit the increase in viscosity, and improve the density of the coating film and the adhesion to the base layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251404230000061
    Figure BDA0005251404230000061
  • Figure BDA0005251404230000101
    Figure BDA0005251404230000101
  • Figure BDA0005251404230000111
    Figure BDA0005251404230000111
Patent Text Reader

Abstract

The invention discloses a polymer emulsion, a preparation method and an application method of the polymer emulsion in preparation of a thick coating type polymer cement coating. The polymer emulsion is prepared from the following raw materials: a monomer, an emulsifier, an initiator and an auxiliary agent, the monomers comprise styrene, butyl acrylate, 2-ethylhexyl acrylate and functional monomers, and the functional monomers comprise acrylamide, methacrylic acid and beta-acryloyloxy propionic acid; the auxiliary agent comprises a retarder and a dispersing agent. When a thick coating type polymer cement coating prepared from the polymer emulsion disclosed by the invention is prepared into a thick coating film, the thick coating cracking condition of the coating can be overcome, and the open time is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cement coatings, and in particular relates to a polymer emulsion, a preparation method and an application method thereof in preparing thick coating type polymer cement coatings. Background Art

[0002] Polymer cement coatings are mainly composed of cement and other powders. When used, they are mixed with liquid materials and applied in thin layers with multiple brushes. They cannot be applied thickly at one time, as this will easily cause cracking. Therefore, multiple applications are required to achieve a certain thickness, which greatly increases the construction cost. The open time of polymer cement coatings refers to the time interval from the start of coating production to the time when the coating maintains construction and its mechanical properties remain stable. Due to the violent hydration reaction of cement, the introduction of polymer emulsions slows down the hydration of cement. In the actual construction process, excessive coating viscosity and short open time will seriously affect the construction progress, and after film formation, it will affect the density of the coating and the adhesion to the base layer.

[0003] In the prior art, Swiss Asada Company disclosed in patent document CN116438266A that it relates to an open time additive composition, which includes at least two different imidazole-containing ketones, and tests the wet edge to open time ratio, open time and touch dryness by changing the substituent to an oleate group to characterize the performance of the open time additive. Hunan Fuxiang Paint Chemical Technology Co., Ltd. disclosed in patent document CN102627898B that it relates to a water-based coating with a long open time and a preparation method thereof, which discloses that an isocyanate polyurethane prepolymer is first prepared, added to an acrylate polymer, and supplemented with powder to prepare a water-based coating with a low VOC content and a long open time and wet edge time, which is particularly helpful for the leveling of the coating surface to obtain a better film-forming effect. However, the auxiliary agent synthesis steps required for the above two methods are complicated and expensive. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a polymer emulsion, a preparation method and an application method thereof in preparing a thick coating type polymer cement coating.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] In one aspect of the present invention, a polymer emulsion is provided, wherein the polymer emulsion is prepared from the following raw materials: a monomer, an emulsifier, an initiator and an auxiliary agent;

[0007] The monomers include styrene, butyl acrylate, isooctyl acrylate and functional monomers, wherein the functional monomers include acrylamide, methacrylic acid and β-acryloxypropionic acid;

[0008] The auxiliary agents include retarders and dispersants.

[0009] In some embodiments, the functional monomer accounts for 2-3% of the total weight of the monomers;

[0010] In some embodiments, the weight ratio of acrylamide, methacrylic acid and β-acryloxypropionic acid in the functional monomer is 1:0.07-0.2:0.07-0.2;

[0011] In some embodiments, the weight ratio of styrene, butyl acrylate, and isooctyl acrylate in the monomer is 13-15:34-35:3.5-4;

[0012] In some embodiments, the emulsifier accounts for 0.39% to 0.62% of the total weight of the polymer emulsion, and includes an anionic emulsifier and a nonionic emulsifier in a mass ratio of 0.9 to 3:1;

[0013] In some embodiments, the initiator accounts for 0.5% to 1% of the total weight of the monomer;

[0014] In some embodiments, the retarder accounts for 0.2% to 0.5% of the total weight of the polymer emulsion;

[0015] In some embodiments, the dispersant accounts for 0.2% to 0.5% of the total weight of the polymer emulsion.

[0016] In some embodiments, the anionic emulsifier is selected from one or two of alkyl diphenyl ether sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate, and ethoxylated alkyl sulfate sodium salt;

[0017] Specifically, alkyl diphenyl oxide sulfonates such as sodium dodecyl diphenyl oxide disulfonate (CAS No. 28519-02-0), ethoxylated alkyl sulfate sodium salts such as sodium laureth sulfate (CAS No. 9004-82-4).

[0018] In some embodiments, the nonionic emulsifier is selected from one or two of ethylene glycol monostearate, ethylene glycol distearate, diethylene glycol monostearate, diethylene glycol distearate, polyethylene glycol 400 monostearate, polyethylene glycol 400 distearate, and polyethylene glycol 6000 distearate;

[0019] In some embodiments, the initiator is a persulfate or an azo initiator;

[0020] In some embodiments, the retarder is selected from at least one of hydroxy acids and their salts, sugar-containing carbohydrates, inorganic salts, and lignin sulfonates.

[0021] Specifically, the retarder includes one or more of hydroxy acids and salts thereof, such as tartaric acid, citric acid, gluconic acid and salts thereof, and salicylic acid, sugary carbohydrates, such as molasses, glucose, sucrose, etc., inorganic salts, such as borates, phosphates, zinc salts, etc., lignin sulfonates, such as wood calcium, wood sodium, etc. Tartaric acid is preferred;

[0022] In some embodiments, the dispersant is an inorganic dispersant and / or an organic dispersant.

[0023] In this embodiment, the inorganic dispersant mainly achieves the purpose of dispersion by changing and increasing the zeta potential of the colloidal particles surface to generate electrostatic repulsion, while the organic dispersant has a smaller effect on the zeta potential of the colloidal particles surface and mainly achieves the purpose of dispersion by steric stabilization.

[0024] In some embodiments, the initiator is sodium persulfate;

[0025] In some embodiments, the inorganic dispersant is selected from at least one of silicates and alkali metal phosphates;

[0026] Specifically, silicates, such as water glass; alkali metal phosphates, such as sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate, etc.

[0027] In some embodiments, the organic dispersant is selected from at least one of triethylhexyl phosphate, sodium lauryl sulfate, methyl amyl alcohol, sodium polyacrylate, cellulose derivatives, polyacrylamide, guar gum, and polyethylene glycol esters of fatty acids.

[0028] In some embodiments, the dispersant is an organic dispersant, preferably BOLIGA BLJ-5018F (polycarboxylate ammonium salt dispersant);

[0029] In some embodiments, the raw materials of the polymer emulsion further include 0.3% to 0.5% of the total weight of the monomers as an oxidant;

[0030] In some embodiments, the raw materials of the polymer emulsion further include a reducing agent accounting for 0.2% to 0.4% of the total weight of the monomers;

[0031] In some embodiments, the raw materials of the polymer emulsion further include 0.1% to 0.3% of a neutralizing agent based on the total weight of the polymer emulsion.

[0032] In some embodiments, the oxidant is selected from one of hydrogen peroxide, tert-butyl hydroperoxide, and cumene hydroperoxide, preferably tert-butyl hydroperoxide;

[0033] In some embodiments, the reducing agent is selected from one of isoascorbic acid, bleaching powder, sodium pyrosulfite, sodium bisulfite, FF6M, L-septic acid, and sodium ascorbate, preferably sodium bisulfite;

[0034] In some embodiments, the neutralizing agent is selected from one of sodium hydroxide, ammonia water, triethylamine, dimethylethanolamine, and 2-amino-2-methylpropanol, preferably sodium hydroxide.

[0035] In another aspect, the present invention provides a method for preparing a polymer emulsion, comprising at least:

[0036] (1) Preparation of pre-emulsion: Mix and stir the emulsifier, monomer and deionized water for 30 minutes to obtain the pre-emulsion;

[0037] (2) Preparation of bottom material: adding deionized water into the reaction kettle to obtain the bottom material;

[0038] (3) Polymerization reaction: adding initiator a to the bottom material of the kettle under stirring, dripping the pre-emulsion after 3 to 10 minutes, and dripping initiator b after 1 to 3 hours, controlling the dripping of the pre-emulsion and the initiator b at the same time, controlling the dripping temperature at 87 to 89° C., and performing heat preservation after the dripping is completed;

[0039] (4) Post-treatment: adding an oxidizing agent and a reducing agent to eliminate residual monomers, adding a neutralizing agent to adjust the pH, and adding an auxiliary agent to obtain the polymer emulsion.

[0040] In step (1), the mass ratio of the amount of the deionized water to the total amount of the monomer is 3 to 3.5:13;

[0041] In step (2), the mass ratio of the amount of the deionized water to the total amount of the monomer is 5 to 6:13;

[0042] In step (3), the ratio of the initiator a to the initiator b is 3:1 to 5:1;

[0043] In step (3), the heat preservation treatment time is 30 to 120 minutes;

[0044] In step (3), the temperature of the heat preservation treatment is 87-89° C.;

[0045] In step (4), the oxidant is added in the form of an aqueous solution;

[0046] In step (4), the reducing agent is added in the form of an aqueous solution;

[0047] In step (4), the neutralizing agent is added in the form of an aqueous solution.

[0048] The third aspect of the present invention also provides an application method of a polymer emulsion in the preparation of a thick-coating polymer cement coating, comprising: preparing the polymer emulsion into a liquid material and stirring and mixing it with a powder material at a liquid-to-powder ratio of 1:1.8 to obtain the thick-coating polymer cement coating.

[0049] The liquid material comprises: polymer emulsion 90% to 99%, H2O 1% to 10%, dispersant SN-Dispersant5040 0.1% to 0.5%, defoamer SN-DEFOAMERNXZ 0.1% to 0.4%;

[0050] The powder material comprises: 30% to 50% of PO42.5 cement, 15% to 25% of 200-mesh quartz powder, 25% to 35% of 80-120-mesh quartz sand, and 10% to 20% of 400-mesh heavy calcium.

[0051] The reagents and raw materials used in the present invention are commercially available.

[0052] The positive and progressive effects of the present invention are:

[0053] 1. The thick-coating polymer cement coating configured with the polymer emulsion of the present invention can achieve the required standard thickness in one-time construction. The present invention also uses a special process to synthesize the polymer emulsion by adjusting the amount and proportion of the emulsifier and the functional monomer. Specifically, the present invention adds a large amount of initiator at the initial stage of the reaction, generates a large amount of primary free radicals after heating, and drips the pre-emulsion after an interval of 3 to 10 minutes. The primary free radicals initiate monomer polymerization in different places to generate latex particles. The polymer emulsion obtained by this process has low viscosity and coarse particle size. It helps to reduce the subsequent initial slurry viscosity. The two-component coating formed by the method of the present invention and a variety of inorganic powders such as cement can shorten the time difference between the drying of the surface and the inside when in use, thereby solving the cracking problem.

[0054] 2. The present invention can reduce the initial slurry viscosity and inhibit the increase of viscosity by adding readily available and inexpensive additives, which can extend the operating time of workers during the actual construction process and bring convenience. DETAILED DESCRIPTION

[0055] The present invention is described in detail below in conjunction with the embodiments, and the technical scheme of the present invention is clearly and completely described to facilitate the understanding of the present invention by those skilled in the art. The described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods not mentioned in detail are process steps or preparation methods known to those skilled in the art.

[0056] Example 1

[0057] Preparation of pre-emulsion: add emulsifier (0.06 parts of sodium lauryl polyether sulfate, 0.216 parts of sodium dodecyl diphenyl oxide disulfonate, 0.1 parts of polyethylene glycol 400 distearate) to 12 parts of deionized water, stir for 10 minutes, add 1.0 parts of acrylamide, 13.2 parts of styrene, 34.17 parts of butyl acrylate, 3.95 parts of isooctyl acrylate, 0.07 parts of methacrylic acid, 0.07 parts of β-acryloxypropionic acid in sequence, and stir at 200-300 rpm for 30 minutes.

[0058] Preparation of the bottom material: Add 22 parts of deionized water into the reactor and heat it to 87-89°C.

[0059] Preparation for polymerization reaction: sodium persulfate initiator (0.21 parts of sodium persulfate dissolved in 0.67 parts of deionized water) was added to the reactor under stirring for 5 minutes, and then the pre-emulsion was added dropwise. After 2 hours, sodium persulfate initiator (0.07 parts of sodium persulfate dissolved in 2.53 parts of deionized water) was added dropwise. The total addition time was 4 hours, and the temperature was maintained at 87-89°C.

[0060] Insulation stage: After the addition is completed, keep warm at 87-89°C for 90 minutes.

[0061] Elimination of residual monomers: Cool down to 78° C., take 0.18 parts of tert-butyl hydroperoxide (dissolved in 2 parts of deionized water) and 0.12 parts of sodium bisulfite (dissolved in 2 parts of deionized water).

[0062] Post-addition: cool to below 40°C, add 0.2 parts of tartaric acid and 0.2 parts of BLJ-5018F, then add 0.1 parts of sodium hydroxide to neutralize the pH to 7-9, adjust the solid content to 55% to obtain a polymer emulsion.

[0063] Slurry preparation: Prepare liquid material according to the liquid material application formula in Table 1. Under stirring, slowly add powder material according to the liquid-to-powder ratio of 1:1.8, and stir at 800 rpm for 5 minutes to obtain the polymer cement coating.

[0064] Table 1 Formulation of polymer cement coating

[0065]

[0066] Example 2

[0067] Preparation of pre-emulsion: add emulsifier (0.1 part of sodium lauryl polyether sulfate, 0.22 part of sodium dodecyl diphenyl oxide disulfonate, 0.16 part of polyethylene glycol 400 distearate) to 12 parts of deionized water, stir for 10 minutes, add 1.0 part of acrylamide, 13.2 parts of styrene, 35.0 parts of butyl acrylate, 3.95 parts of isooctyl acrylate, 0.12 parts of methacrylic acid, 0.2 parts of β-acryloxypropionic acid in sequence, and stir at 200-300 rpm for 30 minutes.

[0068] Preparation of the bottom material: Add 22 parts of deionized water into the reactor and heat it to 87-89°C.

[0069] Preparation for polymerization reaction: sodium persulfate initiator (0.21 parts of sodium persulfate dissolved in 0.67 parts of deionized water) was added to the reactor under stirring for 5 minutes, and then the pre-emulsion was added dropwise. After 2 hours, sodium persulfate initiator (0.07 parts of sodium persulfate dissolved in 2.53 parts of deionized water) was added dropwise. The total addition time was 4 hours, and the temperature was maintained at 87-89°C.

[0070] Insulation stage: After the addition is completed, keep warm at 87-89°C for 90 minutes.

[0071] Elimination of residual monomers: Cool down to 78° C., take 0.25 parts of tert-butyl hydroperoxide (dissolved in 2 parts of deionized water) and 0.16 parts of sodium bisulfite (dissolved in 2 parts of deionized water).

[0072] Post-addition: Cool down to below 40°C, add 0.2 parts of tartaric acid and 0.2 parts of BLJ-5018F, then add 0.15 parts of sodium hydroxide to neutralize the pH to 7-9, and adjust the solid content to 55% to obtain a polymer emulsion.

[0073] Slurry preparation: Prepare liquid material according to the liquid material application formula in Table 1. Under stirring, slowly add powder material according to the liquid-to-powder ratio of 1:1.8, and stir at 800 rpm for 5 minutes to obtain the polymer cement coating.

[0074] Example 3

[0075] Preparation of pre-emulsion: add emulsifier (0.06 parts of sodium lauryl polyether sulfate, 0.216 parts of sodium dodecyl diphenyl oxide disulfonate, 0.16 parts of polyethylene glycol 400 distearate) to 12 parts of deionized water, stir for 10 minutes, add 1.0 parts of acrylamide, 15.0 parts of styrene, 34.17 parts of butyl acrylate, 3.95 parts of isooctyl acrylate, 0.07 parts of methacrylic acid, 0.2 parts of β-acryloxypropionic acid in sequence, and stir at 200-300 rpm for 30 minutes.

[0076] Preparation of the bottom material: Add 22 parts of deionized water into the reactor and heat it to 87-89°C.

[0077] Preparation for polymerization reaction: sodium persulfate initiator (0.28 parts of sodium persulfate dissolved in 0.67 parts of deionized water) was added to the reactor under stirring for 5 minutes, and then the pre-emulsion was added dropwise. After 2 hours, sodium persulfate initiator (0.07 parts of sodium persulfate dissolved in 2.53 parts of deionized water) was added dropwise. The total addition time was 4 hours, and the temperature was maintained at 87-89°C.

[0078] Insulation stage: After the addition is completed, keep warm at 87-89°C for 90 minutes.

[0079] Elimination of residual monomers: Cool down to 78° C., take 0.18 parts of tert-butyl hydroperoxide (dissolved in 2 parts of deionized water) and 0.12 parts of sodium bisulfite (dissolved in 2 parts of deionized water).

[0080] Post-addition: cool to below 40°C, add 0.4 parts of tartaric acid and 0.2 parts of BLJ-5018F, then add 0.13 parts of sodium hydroxide to neutralize the pH to 7-9, and adjust the solid content to 55% to obtain a polymer emulsion.

[0081] Slurry preparation: Prepare liquid material according to the liquid material application formula in Table 1. Under stirring, slowly add powder material according to the liquid-to-powder ratio of 1:1.8, and stir at 800 rpm for 5 minutes to obtain the polymer cement coating.

[0082] Example 4

[0083] Preparation of pre-emulsion: add emulsifier (0.06 parts of sodium lauryl polyether sulfate, 0.22 parts of sodium dodecyl diphenyl oxide disulfonate, 0.1 parts of polyethylene glycol 400 distearate) to 12 parts of deionized water, stir for 10 minutes, add 1.0 parts of acrylamide, 15.0 parts of styrene, 34.17 parts of butyl acrylate, 3.95 parts of isooctyl acrylate, 0.12 parts of methacrylic acid, 0.07 parts of β-acryloxypropionic acid in sequence, and stir at 200-300 rpm for 30 minutes.

[0084] Preparation of the bottom material: Add 22 parts of deionized water into the reactor and heat it to 87-89°C.

[0085] Preparation for polymerization reaction: sodium persulfate initiator (0.35 parts of sodium persulfate dissolved in 0.67 parts of deionized water) was added to the reactor under stirring for 5 minutes, and then the pre-emulsion was added dropwise. After 2 hours, sodium persulfate initiator (0.07 parts of sodium persulfate dissolved in 2.53 parts of deionized water) was added dropwise. The total addition time was 4 hours, and the temperature was maintained at 87-89°C.

[0086] Insulation stage: After the addition is completed, keep warm at 87-89°C for 90 minutes.

[0087] Elimination of residual monomers: Cool down to 78° C., take 0.18 parts of tert-butyl hydroperoxide (dissolved in 2 parts of deionized water) and 0.12 parts of sodium bisulfite (dissolved in 2 parts of deionized water).

[0088] Post-addition: Cool down to below 40°C, add 0.2 parts of tartaric acid and 0.4 parts of BLJ-5018F, then add 0.13 parts of sodium hydroxide to neutralize the pH to 7-9, and adjust the solid content to 55% to obtain a polymer emulsion.

[0089] Slurry preparation: prepare liquid material according to the liquid material application formula in Table 1. Under stirring, slowly add powder material according to the liquid-to-powder ratio of 1:1.8, and stir at 800 rpm for 5 minutes to obtain the polymer cement coating.

[0090] The present invention also provides the following comparative examples.

[0091] Comparative Example 1

[0092] The only difference from Example 1 is that, 1. in the step of preparing the pre-emulsion, 0.07 parts of methacrylic acid and 0.07 parts of β-acryloxypropionic acid are replaced by 0.14 parts of acrylic acid; 2. in the step of post-addition, the weight portion of sodium hydroxide is 0.2 parts.

[0093] Comparative Example 2

[0094] The only difference from Example 2 is that, 1. in the step of preparing the pre-emulsion, the weight portion of butyl acrylate is 34.17 parts; 2. in the step of post-addition, BLJ-5018F is not added, and the weight portion of sodium hydroxide is 0.12 parts.

[0095] Comparative Example 3

[0096] The only difference from Example 3 is that, 1. in the step of preparing the pre-emulsion, the weight portion of polyethylene glycol 400 distearate is 0.3 parts and the weight portion of butyl acrylate is 35.0 parts; 2. in the post-addition step, tartaric acid and BLJ-5018F are not added, and the weight portion of sodium hydroxide is 0.1 parts.

[0097] Comparative Example 4

[0098] The only difference from Example 4 is that, 1. in the step of preparing the pre-emulsion, methacrylic acid is not added; 2. in the step of post-addition, the weight portion of BLJ-5018F is 0.2 parts.

[0099] Comparative Example 5

[0100] The only difference from Example 4 is that, 1. in the step of preparing the pre-emulsion, β-acryloxypropionic acid is not added; 2. in the step of polymerization, 2 parts of the emulsion are added to the reactor together with 0.35 parts of sodium persulfate.

[0101] Comparative Example 6

[0102] Commercially available product, model 7366 produced by Badful Company.

[0103] Product performance testing

[0104] The polymer cement coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 6 were tested, and the test standards or methods were as follows:

[0105] 1. Test of tensile strength and elongation at break: The polymer cement coating prepared in the embodiment and comparative example is poured into the mold specified in the GB / T 16777-2008 standard document for coating. The coating is coated twice. The latter coating should be carried out after the former coating is completely dry. The interval between the two coatings is 12 to 24 hours, so that the coating thickness reaches 1.5±0.2mm. After the surface of the last coating is scraped flat, it is left to stand for 96 hours at a temperature of 23±2°C and a relative humidity of (50±10)%. Then, the sample is demoulded and the reverse side of the sample is placed upward in a drying oven at 40±2°C for 48 hours. After being taken out, it is placed in a desiccator and cooled to room temperature. The sample is punched into a test piece using the CP-25A slicer of Shanghai Dengjie Machinery Equipment. The shape of the test piece is the I-type dumbbell shape specified in the GB / T 528-1998 standard document. The tensile strength and elongation at break of the test piece are tested on the LD23.104 microcomputer-controlled electronic universal testing machine of Shanghai Lishi Scientific Instrument.

[0106] 2. Slurry viscosity test: Based on the simple test method of open time, the present invention adopts the method of testing the change of coating viscosity within a certain time interval to reflect whether the open time is improved. The present invention chooses to use the change of coating viscosity before and after 30 minutes to feedback the quality of the open time. Generally speaking, the smaller the change value of the coating viscosity within 30 minutes, the longer the open time. The specific method is: in a constant temperature and humidity environment (temperature is 25°C, humidity is 50%), the above-prepared coating is tested for initial viscosity (4#30r) with a Brookfield viscometer, and after 30 minutes, the dried skin on the surface is removed, and the coating viscosity (4#30r) is tested again.

[0107] 3. Film test: Apply 2mm and 4mm films on the calcium silicate board to see if there are any cracks after the paint dries.

[0108] The performance of the products prepared in Examples 1 to 4 and Comparative Examples 1 to 6 was tested, and the results are shown in Table 2.

[0109] Table 2 Performance test results

[0110]

[0111]

[0112] As can be seen from Table 2, by comparing Example 1 with Comparative Examples 1 and 4, it can be seen that methacrylic acid and β-acryloxypropionic acid synergistically change the surface properties of the polymer emulsion, so that the surface of the polymer latex particles contains carboxyl groups, and the adsorption capacity on the surface of cement particles becomes stronger, which will enrich calcium ions on the polymer surface through complexation, reduce the internal stress of the cement coating, and thus inhibit the cracking of the coating. However, the coating made of acrylic acid monomer alone will crack when thickly coated.

[0113] From the results of Example 1, Example 3 and Comparative Example 2, the use of flocculant tartaric acid can reduce the value of the initial slurry viscosity, and the more the amount added, the more obvious the reduction effect. However, for coatings with a high liquid-to-powder ratio, the rapid growth of the slurry viscosity in the later stage cannot be suppressed, so the present invention can significantly suppress the increase in slurry viscosity and extend the open time by adding dispersant BLJ-5018F. Comparative Example 3 shows that the lack of flocculant tartaric acid and dispersant BLJ-5018F at the same time makes the initial viscosity of the coating high and the increase is the largest, and the open time is the worst. However, the dosage of these two is also controlled within a certain range, and too much will cause the adhesion between the coating and the substrate to decrease. This may cause the coating to be easy to peel off, fall off or bubble, thereby affecting the durability and quality of the coating. And too much dispersant may destroy the stability of the coating, causing the coating to separate, condense or precipitate. This may cause the coating to lose uniformity and be difficult to apply or use normally.

[0114] From the results of Example 4, Comparative Example 5, and Comparative Example 6, the use of other polymerization processes in Comparative Example 5 has an adverse effect on improving the open time and thick coating crack resistance, while the use of the polymerization process of the present invention can improve the thick coating crack resistance and reduce the value of the coating rise. Although the present invention and the commercially available product 7366 have similar effects in terms of thick coating crack resistance, the viscosity increase value of the present invention is significantly lower than that of the commercially available product 7366 in terms of improving the open time effect. Therefore, the present application is significantly better than the commercially available product 7366 emulsion in improving the open time effect.

[0115] Finally, it should be noted that in the present invention, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements that are inherent to such process, method, article or apparatus.

[0116] Although the present disclosure has been disclosed above through the description of the specific embodiments of the present disclosure, it should be understood that those skilled in the art can design various modifications, improvements or equivalents to the present disclosure within the spirit and scope of the attached scheme. These modifications, improvements or equivalents should also be considered to be included in the scope of protection claimed by the present disclosure.

Claims

1. A polymer emulsion, characterized in that The polymer emulsion is prepared from the following raw materials: monomer, emulsifier, initiator and auxiliary agent; The monomers include styrene, butyl acrylate, isooctyl acrylate and functional monomers, wherein the functional monomers include acrylamide, methacrylic acid and β-acryloxypropionic acid; The auxiliary agents include retarders and dispersants.

2. The polymer emulsion according to claim 1, characterized in that The functional monomer accounts for 2-3% of the total weight of the monomers; and / or, the weight ratio of acrylamide, methacrylic acid and β-acryloxypropionic acid in the functional monomer is 1:0.07-0.2:0.07-0.2; and / or, the weight ratio of styrene, butyl acrylate and isooctyl acrylate in the monomer is 13-15:34-35:3.5-4; and / or, the emulsifier accounts for 0.39% to 0.62% of the total weight of the polymer emulsion, and includes an anionic emulsifier and a nonionic emulsifier in a mass ratio of 0.9 to 3:1; and / or, the initiator accounts for 0.5% to 1% of the total weight of the monomers; and / or, the retarder accounts for 0.2% to 0.5% of the total weight of the polymer emulsion; And / or, the dispersant accounts for 0.2% to 0.5% of the total weight of the polymer emulsion.

3. The polymer emulsion according to claim 2, characterized in that The anionic emulsifier is selected from one or two of alkyl diphenyl ether sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate, and ethoxylated alkyl sulfate sodium salt; And / or, the nonionic emulsifier is selected from one or two of ethylene glycol monostearate, ethylene glycol distearate, diethylene glycol monostearate, diethylene glycol distearate, polyethylene glycol 400 monostearate, polyethylene glycol 400 distearate, and polyethylene glycol 6000 distearate; And / or, the initiator is a persulfate or an azo initiator; and / or, the retarder is selected from at least one of hydroxy acids and salts thereof, sugary carbohydrates, inorganic salts, and lignin sulfonates, preferably tartaric acid; And / or, the dispersant is an inorganic dispersant and / or an organic dispersant.

4. The polymer emulsion according to claim 3, characterized in that The initiator is sodium persulfate; and / or, the inorganic dispersant is selected from at least one of silicates and alkali metal phosphates; And / or, the organic dispersant is selected from at least one of triethylhexyl phosphate, sodium lauryl sulfate, methyl amyl alcohol, sodium polyacrylate, cellulose derivatives, polyacrylamide, guar gum, and polyethylene glycol esters of fatty acids.

5. The polymer emulsion according to claim 3, characterized in that The dispersant is an organic dispersant, preferably BLJ-5018F; And / or, the raw materials of the polymer emulsion further include 0.3% to 0.5% of the total weight of the monomers as an oxidant; And / or, the raw materials of the polymer emulsion further include 0.2% to 0.4% of the total weight of the monomers as a reducing agent; And / or, the raw materials of the polymer emulsion further include 0.1% to 0.3% of a neutralizing agent based on the total weight of the polymer emulsion.

6. The polymer emulsion according to claim 5, characterized in that The oxidant is selected from one of hydrogen peroxide, tert-butyl hydroperoxide and cumene hydroperoxide, preferably tert-butyl hydroperoxide; And / or, the reducing agent is selected from one of isoascorbic acid, bleaching powder, sodium pyrosulfite, sodium bisulfite, FF6M, L-septic acid, sodium ascorbate, preferably sodium bisulfite; And / or, the neutralizing agent is selected from one of sodium hydroxide, ammonia water, triethylamine, dimethylethanolamine, and 2-amino-2-methylpropanol, preferably sodium hydroxide.

7. A method for preparing a polymer emulsion according to any one of claims 1 to 6, characterized in that: The steps include: (1) Preparation of pre-emulsion: Mix and stir the emulsifier, monomer and deionized water for 30 minutes to obtain the pre-emulsion; (2) Preparation of the bottom material: adding deionized water into the reaction kettle to obtain the bottom material; (3) Polymerization reaction: adding initiator a to the bottom material of the kettle under stirring, dripping the pre-emulsion after 3 to 10 minutes, and dripping initiator b after 1 to 3 hours, controlling the dripping of the pre-emulsion and the initiator b at the same time, controlling the dripping temperature at 87 to 89° C., and performing heat preservation after the dripping is completed; (4) Post-treatment: adding an oxidizing agent and a reducing agent to eliminate residual monomers, adding a neutralizing agent to adjust the pH, and adding an auxiliary agent to obtain the polymer emulsion.

8. The method for preparing a polymer emulsion according to claim 7, characterized in that: The preparation method satisfies at least one of the following conditions: In step (1), the mass ratio of the amount of the deionized water to the total amount of the monomer is 3 to 3.5:13; In step (2), the mass ratio of the amount of the deionized water to the total amount of the monomer is 5 to 6:13; In step (3), the ratio of the initiator a to the initiator b is 3:1 to 5:1; In step (3), the heat preservation treatment time is 30 to 120 minutes; In step (3), the temperature of the heat preservation treatment is 87-89° C.; In step (4), the oxidant is added in the form of an aqueous solution; In step (4), the reducing agent is added in the form of an aqueous solution; In step (4), the neutralizing agent is added in the form of an aqueous solution.

9. A method for using the polymer emulsion according to claims 1 to 6 in preparing a thick coating type polymer cement coating, characterized in that: include: The polymer emulsion is prepared into a liquid material and then mixed with a powder material at a liquid-to-powder ratio of 1:1.8 to obtain the thick-coating polymer cement coating.

10. The method for using the polymer emulsion according to claim 9 in preparing a thick coating type polymer cement coating, characterized in that: The liquid material comprises: polymer emulsion 90% to 99%, H2O 1% to 10%, dispersant SN-Dispersant5040 0.1% to 0.5%, defoamer SN-DEFOAMER NXZ 0.1% to 0.4%; And / or, the powder includes: 30% to 50% of PO42.5 cement, 15% to 25% of 200-mesh quartz powder, 25% to 35% of 80-120-mesh quartz sand, and 10% to 20% of 400-mesh heavy calcium.

Citation Information

Patent Citations

  • Water-based paint with long opening time and preparation method thereof

    CN102627898B

  • Open time additive

    CN116438266A

Cited By

  • Polymer emulsion, preparation method therefor, and use method thereof in preparation of high-build polymer cement coating

    WO2026157249A1